2008
DOI: 10.1002/jmv.21123
|View full text |Cite
|
Sign up to set email alerts
|

Is serum uric acid a predictive factor of response to IFN‐treatment in patients with chronic hepatitis C infection?

Abstract: Several factors, including metabolic profile, are predictive of response to standard antiviral therapy in patients with chronic hepatitis C. In a retrospective study, it was investigated whether uric acid, involved in metabolic syndrome, could be included. A total of 153 patients (56.2% males; mean age 45.7 +/- 11.3 years) treated with pegylated-interferon and ribavirin were included. Eighty-five were infected with hepatitis C virus (HCV) genotype 1 or 4 and 68 with genotype 2 or 3. Viral load was >1,000,000 I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
0
10
3
Order By: Relevance
“…Basal plasma uric acid levels were available in 185 patients (Table I), without significant differences between the 102 who achieved SVR and the 83 primary non-responders (Table I). The cut-off point for serum uric acid ≥ 5.8 proposed by Pellicano et al (16) had no predictive role of response in our study, as SVR was obtained by 56.7% and 53.1% of patients under and over the cut off value, respectively.…”
Section: Resultscontrasting
confidence: 73%
See 1 more Smart Citation
“…Basal plasma uric acid levels were available in 185 patients (Table I), without significant differences between the 102 who achieved SVR and the 83 primary non-responders (Table I). The cut-off point for serum uric acid ≥ 5.8 proposed by Pellicano et al (16) had no predictive role of response in our study, as SVR was obtained by 56.7% and 53.1% of patients under and over the cut off value, respectively.…”
Section: Resultscontrasting
confidence: 73%
“…This drawback explains why we can not discuss the role of insulin resistance, which seems very important in determining the failure of antiviral therapy (22,33). However, our results did not confirm the suggested relation between the chance of SVR and basal values for serum uric acid (16) and neutrophil count (34,35).…”
Section: Discussioncontrasting
confidence: 62%
“…We found high UA levels in chronic viral hepatitis (8.51 ± 2.7 mg/dl). A study from Italy has found that high UA levels are associated with poor outcome in chronic viral hepatitis 9 . This may be because high UA indicates ongoing hepatocellular destruction.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, uric acid showed better predictive value than many other variables that have been reported as predictors for treatment response. Previously, Pellicano et al [ 22 ] reported that uric acid was a predictive factor of IFN treatment response for HCV-infected patients. Other studies have demonstrated a significant relationship between hyperuricemia and insulin resistance [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%